Mechanisms of bone remodeling and therapeutic strategies in chronic apical periodontitis - Luo, Xutao; Wan, Qianxue; Cheng, Lei; Xu, Ruoshi (Frontiers in Cellular and Infection Microbiology, 2022)
Chronic periapical periodontitis is a typical oral disease in which periodontal inflammation caused by an odontogenic infection eventually leads to bone loss. Uncontrolled infections often lead to extensive bone loss around the root tip, which ultimately leads to tooth loss. The main clinical issue in the treatment of periapical periodontitis is the repair of jawbone defects, and infection control is the first priority. However, the oral cavity is an open environment, and the distribution of microorganisms through the mouth in jawbone defects is inevitable. The subversion of host cell metabolism by oral microorganisms initiates disease. The presence of microorganisms stimulates a series of immune responses, which in turn stimulates bone healing. Given the above background, we intended to examine the paradoxes and connections between microorganisms and jaw defect repair in anticipation of new ideas for jaw defect repair. To this end, we reviewed the microbial factors, human signaling pathways, immune cells, and cytokines involved in the development of chronic periapical inflammation, as well as concentrated growth factor（CGF） and stem cells in bone defect repair, with the aim of understanding the impact of microbial factors on host cell metabolism to inform the etiology and clinical management of chronic periapical inflammation.